The Impact Of Service Quality And Trust On Customer Loyalty Through Customer Satisfaction Of Millenial Users Of Bca Credit Card In Jakarta Capital City - Fahmi Rizal; Lies Handrijaningsih (Publisher Cv. Inara, 2021)
Banks play important roles in a country's finance. Significant and strategic functions are required to be managed professionally, effectively and efficiently, and properly supporting economic processes in various sectors. Along with the increase needs to spend from consumers, banks as financial companies need to perform competently. This study aims to determine the impacts of service quality and trust in customer loyalty by measuring the satisfaction of Bank BCA credit card millenial customers in Jakarta Capital City of Indonesia. Data collection using primary data with a large sample of 100 respondents aged 26 to 40 years. Primary data was obtained from distributing questionnaires using Likert Scale data on customers who determine satisfaction and loyalty to Bank BCA, and processed using regression analysis and path analysis.The results of this study indicate that service quality, customer value and trust affect customer loyalty stating that they are interested in the services provided by the bank both directly and indirectly to customer satisfaction so that customers show a level of success through customer satisfaction on loyalty.